Student experiences of facilitated asynchronous online discussion boards : Lessons learned and implications for teaching practice. - James, Allison J.; Douglas, Tracy A.; Earwaker, Louise A.; Mather, Carey A. (Journal of University Teaching & Learning Practice v.19 n.5 https://doi.org/10.53761/1.19.5.9, 2022)
As an alliance of academics undertaking blended delivery, we have experienced the challenge of tailoring teaching strategies to different learning styles. Our teaching has evolved, moving from traditional didactic delivery to the utilisation of online technology to accommodate both academic and student expectations. The pressure to teach within constrained resources and issues presented from the COVID-19 pandemic has provided opportunities to optimise educational technology. We identified a gap in genuinely engaged online discussions, observing that pedagogic value was often obscure. This cross-sectional study investigated the opinions and experiences of undergraduate students in four health science online units where asynchronous discussion boards were linked to summative assessment. By assessing discussion posts, students may be motivated to participate further, with student engagement influenced through educator involvement, the discussion purpose and group interactivity. Whilst some students were critical of the value of asynchronous discussion boards, others positively viewed discussions as a platform for peer engagement and information sharing. Discussion boards can provide active learning experiences particularly for online students; however, effective educator involvement and online supportive teaching strategies and practices are crucial to pedagogical success. Based on the key findings from this study we propose implications for practice in a higher education context. [Author abstract]